HUBUNGAN PENGETAHUAN PERILAKU TERHADAP PENCEGAHAN PENYAKIT HIV - Putra Apriadi Siregar; Adinda Gusti Irawan; Zulianty Putri Azizah; Maria Ulpah Sitorus; Lia Saptriana (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
HIV (Human Immunodeficiency Virus) is a virus that attacks white blood cells in the body (lymphocytes) which results in a decrease in human immunity. Knowledge is very important for the community in understanding HIV prevention so that the disease does not spread and affect personal/friends/family. People who have the HIV virus in their blood are called HIV positive or people with HIV look healthy and do not need treatment. In this research method we used a quantitative method with cross sectional which is a descriptive and analytic research method. The results of our questionnaire in the form of a questionnaire were 262 respondents. people, and the age of the respondents 36-55 years amounted to 1 person. The sex of the male respondents was 65 people, and the sex of the female respondents was 197 people. what we have done is that it turns out that the relationship between knowledge and behavior is very closely related because if our knowledge is good enough to know HIV then the behavior of the community is also good and understands. If our behavior is still not in line with knowledge then it will have a negative effect on ourselves Alone. So from this research, quite a lot of people already know, but there are also some people who don't understand it.